2022
DOI: 10.3389/fmed.2022.922299
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics and Its Applications and Progress in Pancreatitis: A Current State of the Art Review

Abstract: Radiomics involves high-throughput extraction and analysis of quantitative information from medical images. Since it was proposed in 2012, there are some publications on the application of radiomics for (1) predicting recurrent acute pancreatitis (RAP), clinical severity of acute pancreatitis (AP), and extrapancreatic necrosis in AP; (2) differentiating mass-forming chronic pancreatitis (MFCP) from pancreatic ductal adenocarcinoma (PDAC), focal autoimmune pancreatitis (AIP) from PDAC, and functional abdominal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…A systematic review by Zhou Y et al [ 51 ] indicated that radiomics exhibits desirable accuracy in the differential diagnosis of pancreatitis and pancreatic cancer, although this conclusion is drawn from a limited number of original studies. Another systematic review by Yan et al [ 52 ] suggested that contrast-enhanced MRI may have more favorable accuracy. Tarján D et al [ 53 ] developed an AI-based early prediction tool for the severity of AP; however, this tool has not been validated with a large number of real cases.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Zhou Y et al [ 51 ] indicated that radiomics exhibits desirable accuracy in the differential diagnosis of pancreatitis and pancreatic cancer, although this conclusion is drawn from a limited number of original studies. Another systematic review by Yan et al [ 52 ] suggested that contrast-enhanced MRI may have more favorable accuracy. Tarján D et al [ 53 ] developed an AI-based early prediction tool for the severity of AP; however, this tool has not been validated with a large number of real cases.…”
Section: Discussionmentioning
confidence: 99%